Automatic electrical failure detection - Chua Ee Yuan (Universiti Malaysia Perlis, 2008)
The title of this project is Automatic Electrical Failure Detection. This project enables to design a Radio Frequency (RF) communication system that will be able to link from some place to PC as monitoring system. However one of the greatest challenges to design a system is dealing with unexpected situations that will cause electrical devices fail to function and cutoff the over current. In particular it is very difficult for a developer to decide how to detect current and handle it. The current detect by sensor will send back to the computer using the RF communication. The current will be analyzed by current level in microcontroller than easy to control the switching from place A to place B by using RF communication system. This project is actually a prototype project that enables to build a fully Automatic Electrical Failure Detection that can be easy to control the switch by using a RF communication system. The system will auto cutoff current if over the current setting spec and avoidance system prevent collisions. The ultimate goal is to monitor and auto cut off over current to protect the electrical devices.